Hambatan Ibu Tunggal (Single Mother) dalam Pemenuhan Kebutuhan Ekonomi Keluarga di RT 02 Kelurahan Kampung Bali, Kota Bengkulu - Isnenda Cendekiarti; Tamrin Bangsu; Desy Afrita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe the obstacles that exist among single parents. This research uses qualitative research with a phenomenological approach. The subjects in this research were AL and SS. The methods used in collecting data were interviews and observation. The data analysis techniques used are data reduction, data display, and data verification. Test the validity of the data using data triangulation techniques, namely method triangulation. Subject AL experienced problems in the aspect of caring for and educating children, while subject SS experienced problems in the economic aspect. But there are several problems that are felt by both subjects, namely psychological problems and social problems. Both subjects felt the downturn in the early days of being a single parent and felt that their time for their children was decreasing.